Analisis Kepuasan Masyarakat Pada Layanan SKTM di Kantor Desa Bangunrejo Kecamatan Semaka Kabupaten Tanggamus - Sartika Bunga; Heru Wahyudi (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
The purpose of this study was to determine the level of community satisfaction on the quality of services carried out by the village apparatus of Bangunrejo sub-district, Semaka district, Tanggamus district in providing services for making SKTM (Certificate of Disability). The research method used in this research is descriptive qualitative. Qualitative descriptive research is research that aims to describe and describe the conditions that occur in the field. The research technique uses primary data obtained from distributing questionnaires to the people of Bangunrejo village who have taken care of the SKTM for the last 2 years (2020-2021), as many as 369 residents. The theory used is Hardiansyah (2011) which states that community satisfaction is formed because of good service quality where the service is in accordance with community expectations. Good service quality consists of 5 dimensions, namely: responsiveness, reliability, attention, assurance, and physical ability. The results of the respondents' responses to the highest community satisfaction came from the dimensions of reliability and attention. While the dimension that has the lowest level of satisfaction comes from the dimension of physical ability.